22.0k views
1 vote
Options
A. 1/49
B.1/14
C.49
D.14

Options A. 1/49 B.1/14 C.49 D.14-example-1

1 Answer

3 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ 7^{-(5)/(6)}\cdot 7^{-(7)/(6)}\implies 7^{-(5)/(6)-(7)/(6)}\implies 7^{(-5-7)/(6)}\implies 7^{(-12)/(6)}\implies 7^(-2)\implies \cfrac{1}{7^2}\implies \cfrac{1}{49}

User Bruceceng
by
4.6k points